Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/10428194.2016.1219901
|View full text |Cite
|
Sign up to set email alerts
|

Concomitance of monosomal karyotype with at least 5 chromosomal abnormalities is associated with dismal treatment outcome of AML patients with complex karyotype – retrospective analysis of Polish Adult Leukemia Group (PALG)

Abstract: Monosomal karyotype (MK) and complex karyotype (CK) are poor prognostic factors in acute myeloid leukemia (AML). A comprehensive analysis of cytogenetic and clinical factors influencing an outcome of AML-CK was performed. The impact of cladribine containing induction on treatment results was also evaluated. We analyzed 125 patients with AML-CK treated within PALG protocols. MK was found in 75 (60%) individuals. The overall complete remission (CR) rate of 66 intensively treated patients was 62% vs. 28% in CK MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the SWOG study MK has been identified in 20% of patients older than 60 but in only 4% of patients aged 30 or younger . Results of PALG retrospective analysis regarding a population of AML patients with a complex karyotype have shown that addition of cladribine to the standard DA regimen improves OS only in MK − but not in MK + cytogenetic group . Other explanation may be the fact that AML in the elderly exhibits several other biological features associated with chemoresistance, including frequent involvement of a more immature leukemic precursor clone or multidrug resistance mediated by MDR1/P‐glycoprotein …”
Section: Discussionmentioning
confidence: 99%
“…In the SWOG study MK has been identified in 20% of patients older than 60 but in only 4% of patients aged 30 or younger . Results of PALG retrospective analysis regarding a population of AML patients with a complex karyotype have shown that addition of cladribine to the standard DA regimen improves OS only in MK − but not in MK + cytogenetic group . Other explanation may be the fact that AML in the elderly exhibits several other biological features associated with chemoresistance, including frequent involvement of a more immature leukemic precursor clone or multidrug resistance mediated by MDR1/P‐glycoprotein …”
Section: Discussionmentioning
confidence: 99%
“…8 Numerous studies have subsequently confirmed this association. [9][10][11][12][13][14][15][16][17][18][19][20][21] While results with allogeneic HCT appear better than with non-HCT post-remission therapies, several studies -including one from our institution -have reported poor post-HCT outcomes for adults with MK AML. [10][11][12]14,15,[18][19][20][21][22] Based on these data, it is now generally accepted that having MK AML is an important adverse prognostic factor for patients undergoing allogeneic HCT.…”
Section: Introductionmentioning
confidence: 87%
“…As of today, the molecular and cytogenetic alterations of AML cells are being studied in detail ( Dohner, Weisdorf & Bloomfield, 2015 ; Wierzbowska et al, 2017 ; Zhang et al, 2016 ). According to the national comprehensive cancer network (NCCN) guideline, cytogenetic subgroups are classified as favorable, intermediate, and unfavorable risk ( O’Donnell et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%